Vertical Green 2.0 - The Good, the Bad and the Science - Hoffmann, Karin A.; Schröder, Sebastian; Nehls, Thomas; Pitha, Ulrike; Pucher, Bernhard; Zluwa, Irene; Gantar, Damjana; Suklje Erjavec, Ina; Kozamernik, Jana (Universitätsverlag der Technischen Universität Berlin, 2023)
Vertical Greenery Systems (VGS) as systemic, nature-based solution can contribute to the quality of urban space and resilience to climate change. However, there are challenges and reservations about its performance and realization. This book discusses perspectives of urban stakeholders, design and maintenance, potentials regarding food, water, and energy as well as governance, planning and financing. It joins findings from the transnational research project "Urban Vertical Green 2.0".